General concerns on the judicial supervision limits of the due process in the procedures before the inquiry commissions in the Congress - Landa Arroyo, César (2014)
In the last years, there is a gradually participation of the Judicial Branch in the Congress competences and functions to supervise and inquire into issues of public interest. As a result, it has questioned the separation of powers principle. In that context, this article focuses on analyzing what the judicial supervision limits of the due process in the procedures before the inquiry commissions in the Congress are.